G364(P) Delays to diagnosis of childhood cancer: a qualitative study of specialist health care professionals' views. (12th March 2018) - Bowyer, H; Girling, M; Exley, C; Tweddle, D
Abstract : Aims: Specialist health care professionals (SHCPs) working in Paediatric Oncology Principle Treatment Centres (PCTs) can provide invaluable insights into diagnostic pathways and the consequences of delays in diagnosis of childhood cancer. This study is the first to explore their views on the significance of delays in diagnosis of childhood cancer and reports their suggestions of how delays could be reduced. Methods: Semi-structured interviews were conducted with 20 SHCPs working in a variety of paediatric oncology specialist roles within PCTs throughout the UK. SHCPs included clinicians, nurses and allied healthcare professionals. Interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Results: SHCPs believe that delays in diagnosis childhood cancer can have important psychological and physical consequences. They believe there are many barriers to an efficient childhood cancer diagnosis within the UK, but especially within the primary-care setting. They recognise that the rarity of childhood cancer and the variability of presenting symptoms may make raising awareness a challenge. SHCPs instead would like to see changes to how community paediatric healthcare is delivered, suggesting the UK re-consider the introduction of primary-care paediatricians and routine surveillance of children. Conclusion: SHCPs believe that considerable changes to how paediatric healthcare is delivered in the UK could improve overall childhood health, but could also reduce delays in diagnosis of many conditions including cancer. Acknowledgement: This study was fully funded by Cancer Research UK and was supported by Children's Cancer and Leukaemia Group (CCLG).